2006
DOI: 10.1021/ja064637f
|View full text |Cite
|
Sign up to set email alerts
|

Dienamine Catalysis:  Organocatalytic Asymmetric γ-Amination of α,β-Unsaturated Aldehydes

Abstract: A new concept in organocatalysis is presented, the direct asymmetric gamma-functionalization of alpha,beta-unsaturated aldehydes. We disclose that secondary amines can invert the usual reactivity of alpha,beta-unsaturated aldehydes, enabling a direct gamma-amination of the carbonyl compound using azodicarboxylates as the electrophilic nitrogen-source. The scope of the reaction is demonstrated for the enantioselective gamma-amination of different alpha,beta-unsaturated aldehydes, giving the products in moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
259
1
19

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(295 citation statements)
references
References 47 publications
14
259
1
19
Order By: Relevance
“…The same generic outcome was found when using the respective Jørgensen and Hayashi catalysts, 22 which, in addition to the observed conjugate addition of amines to methyl vinyl ketone 22, 25 explains the lack of e.e. and poor catalytic performance (see above).…”
Section: Methodssupporting
confidence: 63%
“…The same generic outcome was found when using the respective Jørgensen and Hayashi catalysts, 22 which, in addition to the observed conjugate addition of amines to methyl vinyl ketone 22, 25 explains the lack of e.e. and poor catalytic performance (see above).…”
Section: Methodssupporting
confidence: 63%
“…26,27 When these conditions were applied to α,ß-unsaturated aldehydes, complex mixtures of peroxides were observed that could not be separated. We expected the formation of dieneamines, as described in the work by Jørgensen et al 28,29 Obviously, we were not able to trap these dienes with singlet oxygen. Thus, the reaction conditions were modified and the photooxygenation was designed as a delayed step.…”
Section: Resultsmentioning
confidence: 84%
“…The result suggested that cyclic amines with moderate alkalinity and two active centers exhibited high activity. Plausible pathways are shown in Scheme 2 and we consider that the ratio of the aldol condensation was promoted by the hydrogen bonding between the amino group or the hydroxy group of 3-pyrrolidinamine or 3-pyrrolidinol and the aldehyde [24,25]. …”
Section: Resultsmentioning
confidence: 99%